Indirect Treatment Comparison between Ribociclib Combined with Non-Steroidal Aromatase Inhibitors and Ovarian Function Suppression vs. Tamoxifen in Premenopausal Women with Early Breast Cancer - Lüftner, Diana; Banys-Paluchowski, Maggie; Hartkopf, Andreas D.; Hörner, Manuel; Janni, Wolfgang; Langanke, Dagmar; Müller, Volkmar; Schneeweiss, Andreas; Schmidt, Marcus; Thill, Marc; Untch, Michael; Wöckel, Achim; Höllrich, Lukas; Kreuzeder, Julia; Marx, Almuth; Meinzinger, Julia; Regus-Leidig, Hanna; Roos, Christian; Wohlgemuth, Hien; Sussmann, Stephanie; Fasching, Peter A. (Geburtshilfe und Frauenheilkunde, 2025)
This study provides an indirect treatment comparison of ribociclib combined with non-steroidal aromatase inhibitors and ovarian function suppression (ribociclib + NSAI + OFS) vs. a frequently used treatment option in German clinical routine (tamoxifen ± OFS) in premenopausal patients with HR-positive (HR+), HER2-negative (HER2−) early breast cancer (BC).Data on premenopausal women treated with ribociclib and tamoxifen were derived from the NATALEE clinical trial (NCT03701334) and the retrospective German data collection CLEAR-B, respectively. NATALEE trial eligibility criteria were applied to the CLEAR-B dataset. Standardized mortality ratio weights were used for propensity score (PS) adjustment to balance study populations. All hazard ratios (HR) were calculated based on a 4-year-observation period for both treatment arms. Effectiveness endpoints comprised invasive and distant disease-free survival (iDFS, dDFS), recurrence-free survival (RFS), and overall survival (OS). Safety-related endpoints were treatment termination (TT) and toxicity-related TT (TTtox). For safety comparisons, the ribociclib arm was divided into groups that discontinued ribociclib + NSAI + OFS or ribociclib only.Significant beneficial effects favoring ribociclib + NSAI + OFS (n = 1115) over tamoxifen ± OFS (n = 822) were observed for all effectiveness outcomes (iDFS [HR = 0.5 (95% CI 0.35; 0.71); p < 0.01]; dDFS [HR = 0.52 (95% CI 0.35; 0.77); p = 0.01], RFS [HR = 0.42 (95% CI 0.29; 0.62); p < 0.01], OS [HR = 0.34 (95% CI 0.18; 0.63); p = 0.01]) during the 4-year-observation period. The effect of early treatment discontinuation showed no significant differences between ribociclib + NSAI + OFS and tamoxifen ± OFS (TT-a: HR = 1.2 [95% CI: 0.71; 2.01], p = 0.48; TTtox-a: HR = 0.54 [95% CI 0.22; 1.30], p = 0.23).In this retrospective analysis, ribociclib + NSAI + OFS demonstrated advantages across all effectiveness endpoints, including OS, in premenopausal women with HR+, HER2− early BC, without increasing overall treatment discontinuation rates compared to tamoxifen ± OFS.
Keywords: ribociclib; indirect treatment comparison; HR-positive; HER2-negative; early breast cancer